DEVELOPMENT OF AN ELECTRONIC DICTIONARY FOR TWO LANGUAGES, ELECTRONIC TRANSLATOR FOR THE ENGLISH AND UZBEK LANGUAGE - Usmonova, Kamola (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
Keeping up with the modern developments is becoming the need of the day and people are finding developments and improvements for their lives in all fields including education or business. One of the developments is the introduction technology in the modern education systems. Linguists are using various complex programs to make analysis of the data they have collected in a few seconds to reach the needed results. This work aims to use ADIOS (Automatic Distillation of Structure) program to make up the algorithm of the sentence structure in English and Uzbek languages. The results show that in most sentence structure cases, there is visible distinction between the two languages in spite of some similarities. So, it concludes that learners need to consider sentence structure while learning and using both languages.